Improved Characteristics of RANKL Immuno-PET Imaging Using Radiolabeled Antibody Fab Fragments - Jonatan Dewulf; Ivanna Hrynchak; Sarah Geudens; Isabel Pintelon; Christel Vangestel; José Sereno; Peter A. van Dam; Antero J. Abrunhosa; Filipe Elvas; Tim Van den Wyngaert (MDPI AG, 2022)
Purpose: RANKL expression in the tumor microenvironment has been identified as a biomarker of immune suppression, negating the effect of some cancer immunotherapies. Previously we had developed a radiotracer based on the FDA-approved RANKL-specific antibody denosumab, [89Zr]Zr-DFO-denosumab, enabling successful immuno-PET imaging. Radiolabeled denosumab, however, showed long blood circulation and delayed tumor uptake, potentially limiting its applications. Here we aimed to develop a smaller radiolabeled denosumab fragment, [64Cu]Cu-NOTA-denos-Fab, that would ideally show faster tumor accumulation and better diffusion into the tumor for the visualization of RANKL. Experimental design: Fab fragments were prepared from denosumab using papain and conjugated to a NOTA chelator for radiolabeling with 64Cu. The bioconjugates were characterized in vitro using SDS-PAGE analysis, and the binding affinity was assessed using a radiotracer cell binding assay. Small animal PET imaging evaluated tumor targeting and biodistribution in transduced RANKL-ME-180 xenografts. Results: The radiolabeling yield of [64Cu]Cu-NOTA-denos-Fab was 58 ± 9.2%, with a specific activity of 0.79 ± 0.11 MBq/µg (n = 3). A radiotracer binding assay proved specific targeting of RANKL in vitro. PET imaging showed fast blood clearance and high tumor accumulation as early as 1 h p.i. (2.14 ± 0.21% ID/mL), which peaked at 5 h p.i. (2.72 ± 0.61% ID/mL). In contrast, [64Cu]Cu-NOTA-denosumab reached its highest tumor uptake at 24 h p.i. (6.88 ± 1.12% ID/mL). [64Cu]Cu-NOTA-denos-Fab specifically targeted human RANKL in transduced ME-180 xenografts compared with the blocking group and negative ME-180 xenograft model. Histological analysis confirmed RANKL expression in RANKL-ME-180 xenografts. Conclusions: Here, we report on a novel RANKL PET imaging agent, [64Cu]Cu-NOTA-denos-Fab, that allows for fast tumor imaging with improved imaging contrast when compared with its antibody counterpart, showing promise as a potential PET RANKL imaging tool for future clinical applications.